Point sources and rays in the phase space: novel tools for optical field modeling - Castaneda, Roman (Photonics Letters of Poland, 2010)
Optical fields in any state of spatial coherence are modelled by using separately radiant and virtual layers of point sources that emit radiant and modulating energies along specific rays in the phase-space representation. The model allows manipulating structured spatial coherence supports individually as required by spatial coherence modulation. It can be implemented in very efficient algorithms on conventional platforms for numerical calculations and simulations as illustrated by examples of interference and diffraction in the case of gratings and slits. Full text: PDF References: R. Castaneda, J. Carrasquilla, "Spatial coherence wavelets and phase-space representation of diffraction", Appl. Opt. 47, E76 (2008). [CrossRef] R. Castaneda et al.,"Radiant, virtual, and dual sources of optical fields in any state of spatial coherence", J. Opt. Soc. Am. A 27, 1322 (2010). [CrossRef] M. Born, E. Wolf, Principles of optics (Oxford, Pergamon Press 1993). R. Castaneda et al.,"Interference in phase space", J. Opt. Soc. Am. A 25, 2518 (2008). [CrossRef] R. Castaneda et al. in press in Appl. Opt. (2010). R. Betancur, R. Castaneda. "Spatial coherence modulation", J. Opt. Soc. Am. A 26, 147 (2009). [CrossRef] R. Betancur et al.,"Beam shaping by spatial coherence modulation based on spatial coherence wavelets", Opt. Las. Eng. 47, 1340 (2009). [CrossRef]